Mechanical and electromagnetic vibrations and waves - Bécherrawy, Tamer (ISTE., 2012)
Dealing with vibrations and waves, this text aims to provide understanding of the basic principles and methods of analysing various physical phenomena. The content includes the general properties of propagation, a detailed study of mechanical (elastic and acoustic) and electromagnetic waves, propagation, attenuation, dispersion, reflection, interference and diffraction of waves. It features chapters on the effect of motion of sources and observers (both classical and relativistic), emission of electromagnetic waves, standing and guided waves and a final chapter on de Broglie wa.